The Position of Source Culture in The Current EFL Textbooks in Indonesia Reflected in 3 Research Findings - Rambe, Maisaroh; Rambe, Laila Afni (English Education: Jurnal Tadris Bahasa Inggris, 2021)
Based on this background, the authors are interested in examining more deeply with research questions, namely why book authors tend to take source culture as material and what are real examples of cultural values reflected in textbooks.The research method used in this study is a qualitative research method with the type of library research. Thus the data collection method used is observation. Observations were made on three journals that have been selected as data for analysis, namely analysis of the cultural content of third grade English textbooks in Cianjur, West Java, Cultural content in Indonesian case English teaching textbooks (ELT), Analysis of cultural content in Pathway textbooks. to English for the second grade of high school. The theory used as an analytical knife is the theory of Cortazzi and Jin (1999) which examines culture. The results of the analysis show that there is a tendency for the authors to choose local culture as a teaching material, as evidenced by 13.11% in Faris journal, 45% in Kurnia journal and 19% in Nurjannah journal who choose source culture as teaching material. The reason the author chooses source culture as source material is because the material is easily understood by the participants of the source culture, the source culture is easily found in real terms, the delivery of the source culture can help preserve the culture itself so that it does not become extinct, the source culture material can broaden students' horizons because of its diversity in Indonesia.Source cultural materials can indirectly foster nature and mutual respect for cultural differences between one another.